Medically Treated Diverticular Abscess Associated With High Risk of Recurrence and Disease Complications. Issue 3 (March 2016) - Devaraj, Bikash; Liu, Wendy; Tatum, James; Cologne, Kyle; Kaiser, Andreas M.
Abstract : BACKGROUND: The best management for diverticulitis with abscess formation remains unknown. OBJECTIVE: The purpose of this study was to determine the natural course and outcomes of patients with medically treated diverticular abscess. DESIGN: We conducted a retrospective review of all patients at our institution with diverticular abscess confirmed by CT from 2004 to 2014. SETTINGS: This study was conducted in a tertiary referral hospital. PATIENTS: A total of 1194 patients were treated for acute diverticulitis in 10 years; 210 patients with CT-documented diverticular abscess were analyzed (140 men (66.7%) and 70 women (33.3%); median age 45 years; range, 23–84 years). MAIN OUTCOME MEASURES: Overall recurrence and disease complication rates, as well as the need for subsequent operation after initial successful nonsurgical management, were measured, along with analysis of the whole cohort and the subgroup of patients with percutaneous drainage for diverticular abscess. RESULTS: During the initial presentation, 25 patients failed nonoperative management and required an urgent operation. A total of 185 patients were initially successfully managed without surgery and were discharged from the hospital. Of these, recurrent diverticulitis developed in 112 (60.5%) after an average time interval of 5.3 months (range, 0.8–20.0 months); 47 patients (42%) experienced more than 1 episode. The modified Hinchey stage at time of recurrence (compared with index stay) increased in 51 patients (45.6%). Seventy one (63%) of 112 recurrences showed local disease complications (recurrent abscess, fistula, stricture, or peritonitis). Fistula formation (colovesicular/colovaginal/colocutaneous) and recurrent abscess were the 2 most frequent complications. Twenty nine (26%) of 112 recurrences required an urgent operation; overall, 66 (59%) of 112 patients eventually underwent surgery at our institution. The original abscess size in patients who later developed recurrences was significantly larger than in patients who did not develop recurrence (5.3 vs 3.2 cm; p < 0.001). Paradoxically, larger abscesses also had a higher chance of successful CT-guided drainage (average size, 6.5 cm; range, 1.1–14 cm), yet CT-guided drainage did not change the overall outcome. Of 65 (31.0%) of 210 patients with CT-guided drainage, 45 (73.8%) of 61 after initial success experienced a recurrence. Furthermore, local disease complications at the time of recurrence were noted in 32 of 61 patients (52.5% of all CT-guided drainage, 71.1% of post-CT–guided drainage recurrences), and 13 (29.2%) of 45 patients with recurrence after successful CT-guided drainage subsequently required an urgent operation. LIMITATIONS: The study was limited by its retrospective noncomparative design. CONCLUSIONS: Diverticular abscesses represent complicated diverticulitis and are associated with a high risk of recurrences and disease complications. Recurrences (contrary to other series) were often more severe than the index presentation. The successful CT-guided drainage of a diverticular abscess does not appear to lower the risks of future recurrence or complication rates and frequently is only a bridge to surgery. After initial successful nonoperative management, patients with diverticular abscess should be offered interval elective colectomy (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A216 ). Abstract : Supplemental Digital Content is available in the text.